The Most Popular Air Microorganisms in the Operating Room in Indonesia: A Literature Review - Andriyanto, Arif; Solikhah, Solikhah; Suryani, Dyah (PROMOTOR, 2024)
Patient safety and prevalence of nosocomial infections are directly related to the problem of airborne germs in the operating room. If not properly controlled, airborne microorganisms can increase the risk of surgical problems and prolong the recovery period, thus jeopardizing patient safety. This disease can also be the cause of nosocomial infections. The main purpose of this study was to determine the most common microorganisms found in operating rooms in Indonesia. By collecting and analyzing data from a variety of literature sources, the study provides a deeper understanding of the composition of airborne microorganisms, the factors that influence them, and their implications for clinical practice and hospital policy. This study collected 37 articles filtered according to inclusion and exclusion criteria using the preferred reporting items for systematic review and meta-analysis (PRISMA) model. It was found that Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli became the most frequently occurring microrganisms. The results of this study have consequences that emphasize the need for better hygiene habits, efficient ventilation systems, and increased awareness of infection risks among medical personnel. The findings of this study are expected to contribute to improving the standard of safety and patient care in hospitals in Indonesia.